THE IMPORTANCE OF USING SONGS AND VIDEOS FOR TEACHING YOUNG LEARNERS - Erkinova , Aziza (Educational Research in Universal Sciences, 2023)
The aim of this study is to examine the importance of using songs in the English language classroom. This study will identify if using songs in the English language classroom will promote vocabulary acquisition, and if using songs in the classroom will motivate the children to learn the English language, and will songs raise the children’s cultural awareness. There is research pointing to the benefits of using music in second language learning however, there exists some disagreement among researchers if music could improve language development or if it is just a fun activity. This article also discusses on how to use music in the classroom in the most valuable way. In the current study, we explore and provide an overview for the possible advantages of using music. It has also been investigated the effectiveness of different musical approaches for facilitating language learning for young children in an educational context. In particular, we will discuss how songs and music can motivate young English language learners in their process and how the second language development can benefit from this.